Mutawasitoh Tahfidzul Qur'an (Mtq) Program For Learning Management At Nurul Huda Purbalingga Islamic Boarding School - Ghopur, Abdul; Imron, Imron (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Abdul Ghopur, Master's Degree Student at Muhammadiyyah University Magelang(UNIMMA) Central Java. This study aims to describe the learning management of theMutawasithoh Tahfidzul Qur'an (Mutiq) Program at the Islamic Islamic Boarding SchoolNurul Huda Purbalingga, starting from lesson planning, learning implementation, andevaluation of learning implementation. This research method uses a qualitativedescriptive approach. The object of this research is the learning management of theMutawasithoh Tahfidzul Qur'an (Mutiq) Islamic Boarding School Nurul HudaPurbalingga. The method of data collection using interviews.The results of research on the learning management of the Mutiq Program at the IslamicBoarding School Nurul Huda Purbalingga show that;First; The lesson plan has been completed with a complete syllabus and LearningImplementation Plan and is well documented in the form of document/book one anddocument/book two, containing the syllabus, lesson plans, annual program and semesterprogram.The Mutiq program for the Islamic Islamic Boarding School Nurul Huda Purbalingga is atype of religious education organized through the wustha/junior high school equivalentlevel education, so that the syllabus and lesson plans refer to equivalence education, plusa local curriculum content typical of pesantren, as well as extracurricular andintracurricular development programs for students. The learning plan is prepared by thePrincipal by involving elements of the foundation, teaching staff, managers, and hasundergone many changes, following the dynamics of government policies and stakeholderrequests.Second; The implementation of the teaching and learning process is carried out onSaturday - Thursday, starting at 07.00 - 13.00 WIB. The learning activity begins with anopening or greeting, the ustadz delivers the subject matter using learning media such asLCD, white board, and markers. The method of delivering material uses the lecturemethod, demonstration, and ends with a question and answer session. Ustadz closed theteaching and learning process by praying together and saying closing greetings.Third; Learning evaluation uses formative evaluation, which is an assessment in the formof a test that is carried out after a subject has been studied by students and summativeevaluation, which is an assessment in the form of a test that is carried out after theteaching and learning process is completed within a certain period of time, namely onesemester and than result for this research is good and effective.